PHYSIOTHERAPEUTIC TREATMENT OF FEMALE URINARY INCONTINENTIA IN A UROGYNECOLOGY UNIT (Cuestiones de Fisioterapia, 2003)
Over the last years, Physiotherapy is considered as fundamental within the female stress urinary incontinence treatment. With this article we intend, on the one hand, to describe the functioning of an Urogynecology unit, where the physiotherapist co-works with other specialists, and on the other hand, to present the therapy results on 412 women who have been treated throughout the last four years. We present very satisfactory global results making patients save themselves, in many of the cases, from the surgery or, in the worse of the cases, taking them in better conditions towards the operation.